Comparendo o multa por incumplir el aislamiento: ¿abuso de autoridad o prevaricato? (2020)
This article proposes legal reflections on the application of regulations issued in connection to the compulsory preventive isolation aimed at preventing the spread of the Covid-19 virus. Likewise, this article touches upon the problems that arise due to the inadequate application of the concept of police orders, through which a mulct or fine is imposed after failing to comply with the parameters established in the decrees. When establishing the practical application of presidential or mayors’ decrees (in the municipal context) the police authorities are in a state of uncertainty when trying to comply with the parameters of their professional practice, as they may be violating principles and rights.